Sabbatical report, Spring 2016 - Vancour, Michele L. (2016)
Keywords: dept.pch; faculty_collection

HIV medication adherence programs: The importance of social support - Breny Bontempi, J.M.; Burleson, L.; Lopez, M.H. (A Cross Section of Nursing Research: Journal Articles for Discussion and Evaluation, 2016)
Since the advent of medical treatments for HIV, the promotion of adherence to these difficult treatment regimens has proven critical to disease management. Three Connecticut state-funded HIV medication adherence programs were evaluated. The purpose of this process evaluation was to explore and compare the goals and modality of each adherence program, assess client and staff satisfaction, and provide recommendations for the improvement of these programs. Focus group interviews with clients and individual interviews with staff were conducted at each of the programs. Interviews were transcribed, coded, and analyzed with a code-and-retrieve method of theme identification. Focus group themes included the importance of social support on medication adherence and the “lifesaving” effect the program has had. The staff expressed that although complete adherence should be the long-term objective, more intermediate objectives should be considered (e.g., behavioral changes to increase clients’ ability, selfesteem, and self-efficacy to take medications). © 2014, 2011, 2008, 2005, 2003, 2001 by Taylor & Francis.
Keywords: dept.pch

Gaps in medical marijuana policy implementation: Real-time perspectives from marijuana dispensary entrepreneurs, health care professionals and medical marijuana patients - Lamonica, Aukje K.; Boeri, Miriam; Anderson, Timothy (Drugs: Education, Prevention and Policy, 2016)
Aims: There is a need for greater understanding of the recursive processes involved in drug policy development and its impact on stakeholders. The aim of this study was to examine the challenges of implementing marijuana policy in Massachusetts, where recent policy shifts have occurred. Methods: Qualitative data were generated from ethnographic field notes, media reports, public records and in-depth interviews with 25 stakeholders, including six medical marijuana dispensary entrepreneurs, eight health care professionals and 11 medical marijuana patients. Data were triangulated using a grounded theory approach. Findings: Stakeholders expressed confusion and misunderstanding, and demonstrated that they held conflicting interpretations of the policy and regulations. Analyses revealed gaps in policy development and implementation that are organised by three specific core implementation processes and the themes of transparency, communication and education. Conclusions: Findings show a need for more transparency in implementation processes, a more effective mode of communicating regulations, and a comprehensive plan for medical marijuana education. Based on our findings, we provide recommendations to help policymakers in the US and other countries considering legalisation of marijuana or other drugs.
Keywords: Cannabis; dept.pch; drug education; education; ethnography; health care provider; policy; public health; qualitative research

“How should I be?” A photovoice exploration into body image messaging for young women across ethnicities and cultures - Madden, Devin; Breny, Jean M (Health Promotion Practice, 2016)
Photovoice, a community-based participatory research method that allows participants to inform research questions in an intimate way, has proven successful with youth. A diverse group of teenage girls living in New York City were asked to take photographs and reflect on what messages they received and from whom, how these messages translate across cultures and ethnicities, and how these messages are internalized and acted on. The group selected specific photographs to discuss together and themes emerged to answer the research questions; themes were reinforced by journal responses and agreed on by the group at the concluding session. The participants identified the media, peers, and family as cultural influencers on body image but noted that these messages change depending on the delivering medium. Participants not only offered recommendations with policy implications for advertising and media giants but also urged public health practitioners, teachers, and other key stakeholders working with young women of color to simply provide them with more space for talking. While Photovoice served as an effective methodology for gaining a more expansive understanding of how body image messages are received with young women of color, the tool should be considered for youth development interventions that take a community-based participatory approach. © 2015, © 2015 Society for Public Health Education.
Keywords: *Body Image/px [Psychology]; *Ethnic Groups/px [Psychology]; *Photography; Adolescent; Body Image; Community-Based Participatory Research; Culture; Ethnic Groups; Family; Female; Humans; Mass Media; New York; New York City; Peer Group; Photography; Stereotyping; Young Adult; adolescence; adolescent; adolescent health; advertising; body image; child; child/adolescent health, health promotion; cultural anthropology; dept.pch; doctor patient relation; ethnic group; ethnicity; family; female; girl; health promotion; health research; human; human experiment; mass medium; medical research; participatory research; peer group; peer-reviewed; photography; psychology; public health; qualitative research; stereotyping; teacher; transcription regulation; women's health; women’s health; young adult

Predictors of types of caregiver burden - Unson, Christine; Flynn, Deborah; Haymes, Elayne; Sancho, Diane; Glendon, Mary Ann (Social Work in Mental Health, 2016)
This study identified the types of caregiver stress and the caregiver and care management characteristics that are associated with this stress. 169 caregivers were recruited from a variety of community settings that cater to caregivers in a New England metropolitan area. They completed the Zarit Burden Interview (ZBI) and a questionnaire concerning their care recipient and caregiving arrangements. Principal Components Analysis on the ZBI resulted in five factors: personal strain/loss, uncertainty/inadequacy, social strain/embarrassment, anger, and dependency. The average age of the caregiver was 59.95 years (SD = 11.75) and the average age of the CR was 83.44 years (SD = 7.88). Of the 169 caregivers, 82% were women, 61.5% daughters/in-law or wives (12.9%), 34.3% were solo caregivers; 16.8% little or no burden, 39.9% reported mild to moderate burden, 35% moderate to severe burden, and 8.4% had severe burden. Dependency (22.4%) and personal strain/loss (13.7%) had the highest proportions reported as “often” to “nearly always.” The ZBI was predicted by only two caregiver characteristics, indicating that it is not sensitive to the experiences of different types of caregivers. Caregivers experience different types of burden depending on their gender, kinship roles, and levels of involvement in the care of their older relative. Solo caregiver status and age (younger) significantly predicted most if not all 5 burden types. Solo and young caregivers experienced the highest levels of caregiver burden. Social work practice must identify the caregiver’s life stage and other and self-expectations in relation to dependency, personal loss, embarrassment, anger, or uncertainty. © 2016 Taylor & Francis.
Keywords: Caregiver burden; United States; adult; aged; anger; caregiver burden; controlled study; dependency; dept.nur; dept.pch; expectation; female; gender; human; human experiment; interview; male; principal component analysis; questionnaire; recipient; social work practice; strain; uncertainty